FENOMENA BULLIYING DI SEKOLAH DALAM PERPEKTIF HUKUM - Ghofar Maulana Arif (JOURNAL IURIS SCIENTIA, 2024)
Schools must be a comfortable and safe place for students to attend school. However, this does not rule out the possibility that several incidents and occurrences will occur that could endanger student safety, especially bullying at school. Bullying itself is a form of oppression or violence carried out intentionally by one person, or carried out continuously by a group of people who are stronger or more powerful than other people, with the aim of harming them. The punishment system for perpetrators of bullying stipulates that children under the age of 12 will not be prosecuted, that children aged 12 but still under 18 cannot face criminal charges and adults can be criminally prosecuted as well as acts. Bullying is often experienced by many people, especially minors. Children are the heirs of the nation and the younger generation who realize the nation's ideals. Therefore, it is very important to maintain the child's growth and development process. If children often receive harsh treatment or are exposed to acts of violence during their growth and development, the process of character formation will be disrupted. Protection of children from violence is mandated by Article 28B paragraph (2) of the 1945 Constitution which basically states that children have the right to survival, growth and development, and protection from violence and discrimination. Many incidents of bullying have occurred and have caused serious impacts such as depression and even claimed lives. Therefore, forms of treatment and protection are preventive and repressive. This research uses a normative juridical legal methodology that combines legal and conceptual approaches.